Economic assessment of access to drinking water and its effect on health in the Nueva Sullana Human Settlement, Piura - Rivera, M (2022)
The objective of this research was to estimate the average willingness to pay of the families of the Nueva Sullana Human Settlement for the sustainability of a project for the creation and installation of the drinking water and sanitation service, through the contingent valuation method with question formats. referendum type, which consists of asking the citizen if they are willing or not to pay for the improvement of the drinking water service through the execution of a project in a hypothetical scenario, and the double limit format that, unlike the first, consists of incorporate a second question (about willingness to pay with a lower or higher value) to the one initially raised, a method that reduces the information bias to negative responses with open formats. The data was obtained through a survey of 112 residents of the area. To estimate the socioeconomic determinants of willingness to pay and economic value, the Logit probabilistic model and statistical inference were used. The results indicate that the socioeconomic factors that affect the decision to pay are: the hypothetical price, family income, age and education. It was estimated that the average willingness to pay of families is S/ 3.85 and S/ 3.22 monthly per family using both methods. There is a positive relationship between ability to pay and willingness to pay. The results of the research are important tools for public managers that allow improving the basic services of the population.